A Comparative Research and Analysis of the Development of Sustainable Tourism in Georgian and other International Curricula - Tamar Koblianidze; Nino Sachaleli (European Scientific Journal, ESJ, 2024)
In  recent years, sustainable development has become an important part of educational systems, beginning from primary schools to universities. Consequently, it has evolved into a societal priority. In 2019, the UNESCO adopted the ESD for 2030 framework with the overall objective of building a more just and sustainable world through the achievement of the 17 Sustainable Development Goals. Education for sustainable development for 2030 framework identifies 5 priority action areas: policy, education and training settings, educators, youth, and communities. Sustainable tourism development has been a commonly used term for many years and is, therefore, an important concept for consideration within tourism degree courses/programs. Based on qualitative research and case study method, this paper focuses on discussing the undergraduate and graduate programs in the context of teaching sustainable tourism in foreign countries, which are compared with the experience of the Georgian Technical University. The aim of the research was to study current educational programs related to sustainable tourism and highlight its importance. In conclusion, it can be asserted that sustainable tourism programs are experiencing a growing demand, with various types of policies being developed. However, the program at the Georgian Technical University stands out on an international scale, having no analogue and being truly unique. At the same time, the results indicate that in many cases, sustainability pedagogy/teaching methods, such as systems and holistic thinking, are not yet widely adopted and are in the process of implementation.